2010
DOI: 10.1073/pnas.1009459107
|View full text |Cite
|
Sign up to set email alerts
|

Prenatal undernutrition and cognitive function in late adulthood

Abstract: At the end of World War II, a severe 5-mo famine struck the cities in the western part of The Netherlands. At its peak, the rations dropped to as low as 400 calories per day. In 1972, cognitive performance in 19-y-old male conscripts was reported not to have been affected by exposure to the famine before birth. In the present study, we show that cognitive function in later life does seem affected by prenatal undernutrition. We found that at age 56 to 59, men and women exposed to famine during the early stage o… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

5
235
2
2

Year Published

2012
2012
2018
2018

Publication Types

Select...
5
4
1

Relationship

0
10

Authors

Journals

citations
Cited by 325 publications
(244 citation statements)
references
References 38 publications
5
235
2
2
Order By: Relevance
“…Our findings are in line with a study showing that late-middle-aged persons, affected by exposure to famine before birth, had poorer executive functioning than those not affected. 31 Better than expected cognitive performance in the presence of brain pathology has been observed in the context of the cognitive reserve hypothesis. 10 The concept of cognitive reserve provides an explanation for differences between individuals in susceptibility to agerelated brain changes or pathology, whereby some people, for example, those with higher educational achievement, can tolerate more of these changes than others and maintain function.…”
Section: Discussionmentioning
confidence: 99%
“…Our findings are in line with a study showing that late-middle-aged persons, affected by exposure to famine before birth, had poorer executive functioning than those not affected. 31 Better than expected cognitive performance in the presence of brain pathology has been observed in the context of the cognitive reserve hypothesis. 10 The concept of cognitive reserve provides an explanation for differences between individuals in susceptibility to agerelated brain changes or pathology, whereby some people, for example, those with higher educational achievement, can tolerate more of these changes than others and maintain function.…”
Section: Discussionmentioning
confidence: 99%
“…Moreover, recent works, studying the effect of external shocks (famine, epidemics, war, etc.) during fetal life and early childhood, have demonstrated that lack of resources has detrimental and durable effects on a range of outcomes later in life: health problems (Lin & Liu, 2014), attention deficits (de Rooij, Wouters, Yonker, Painter, & Roseboom, 2010), anti-social behaviours (Neugebauer, 1999), lower educational level (Lavy, Schlosser, & Shany, 2016), or lower probability of being married and getting a job (Almond, Edlund, Li, & Zhang, 2007). Hence, while life-history strategies remain flexible in the face of new information, at least part of the effect of childhood harshness measured here might reflect conditional adaptations to early life conditions.…”
Section: Discussionmentioning
confidence: 99%
“…It has been shown in animal and more recently in human studies that nutrition is one of the most salient environmental factors, and that nutrition can have a direct effect on gene expression (Levi and Sanderson, 2004;Rosales et al, 2009;Attig et al, 2010;Lillycrop and Burdge, 2011;Jiménez-Chillarón et al, 2012). One of the first and best known human studies in the rapidly growing field of "Nutritional Epigenomics" relates to the Dutch Hunger Winter during the 1940's in which the offspring of mothers exposed to famine during pregnancy had an increased risk of cardiovascular, kidney, lung, and metabolic disorders and reduced cognitive functions (Roseboom et al, 2006;De Rooij et al, 2010). More specifically, evidence has been obtained of hypo-and hyper-methylated DNA segments from the blood cells of the affected individuals (Heijmans et al, 2008).…”
Section: Brain Development In Humansmentioning
confidence: 99%